Personal Psychodynamics of Complications - Vogelzang, Robert L. (Seminars in Interventional Radiology, 2019)
Complications are an uncommon but psychologically difficult aspect to any procedural specialty. Being able to deal with the personal aspect of complications and having the tools to learn from and grow from complications are vital aspects of the practice of radiology. This article discusses the psychodynamics of complications that occur in interventional radiology and proposes some coping mechanisms to deal with these adverse events.
Keywords: complication; interventional radiology; psychology; wellness; burnout